2015
DOI: 10.1007/s00464-015-4585-z
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the need for routine esophagram after peroral endoscopic myotomy (POEM)

Abstract: In this series, we found routine esophagram to have a high sensitivity but a very low specificity in detecting clinically significant complications. Routine esophagram after POEM may not be necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 22 publications
0
20
0
Order By: Relevance
“…Mucosal defects may cause life‐threatening AE such as mediastinitis or peritonitis. Although contrast esophagram is done by approximately 88% of facilities to detect esophageal leaks after POEM, 10 this technique is known to have a suboptimal diagnostic yield to detect clinically significant complications 16 . Esophageal leaks on esophagram may not be detected on POD 1 because dehiscence or mucosal breakdown can take several days to occur 17 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mucosal defects may cause life‐threatening AE such as mediastinitis or peritonitis. Although contrast esophagram is done by approximately 88% of facilities to detect esophageal leaks after POEM, 10 this technique is known to have a suboptimal diagnostic yield to detect clinically significant complications 16 . Esophageal leaks on esophagram may not be detected on POD 1 because dehiscence or mucosal breakdown can take several days to occur 17 .…”
Section: Discussionmentioning
confidence: 99%
“…Although contrast esophagram is done by approximately 88% of facilities to detect esophageal leaks after POEM, 10 this technique is known to have a suboptimal diagnostic yield to detect clinically significant complications. 16 Esophageal leaks on esophagram may not be detected on POD 1 because dehiscence or mucosal breakdown can take several days to occur. 17 Although a recent study reported that POEM could be done as an outpatient procedure with same-day discharge without conducting post-POEM esophagram nor endoscopy, it showed two out of 101 patients with elevated temperature and white blood cell, which consequently revealed mucosal perforation.…”
Section: Discussionmentioning
confidence: 99%
“…Patients are given clear liquids on the evening of surgery if they are not experiencing significant nausea. We no longer perform a routine esophagram in the immediate post-operative period, as we’ve previously demonstrated its low specificity for clinically relevant complications 42 . However, we recommend that novice practitioners obtain routine esophagography during their early POEM experience.…”
Section: Methodsmentioning
confidence: 99%
“…Botulinum toxin injection will last only for a few months, and commonly requires repeated therapy[ 86 , 87 ]. Surgical myotomy can result in durable improvement, whilst POEM may offer a less invasive approach, although long-term data is currently unavailable[ 88 , 89 ]. Medications such as oral nitrates or calcium channel blockers lack efficacy but can be used as a holding measure while definitive therapy is being considered[ 87 ].…”
Section: Treatmentmentioning
confidence: 99%